Konsep Moral dalam Perspektif Masyarakat Islam dan Kristen di Desa Simundol Kecamatan Dolog Sigompulon Kabupaten Padang Lawas Utara - Ritonga, Umma Yanti (Lembaga Yasin AlSys, 2023)
This research is entitled the concept of morals in the perspective of Muslim and Christian communities in Simundol Village, Dolok Sigompulon District, North Padang Lawas Regency. This is field research with the background of an understanding that morality is a tool possessed by humans to regulate the order of life in the world, both in dealing with fellow human beings, other creatures, and His divine nature. Here it can be seen in terms of moral relations in which every human being should be based on three things, namely logic, morals, and aesthetics. This research uses the type of research conducted by researchers is qualitative research with an anthropological approach. This research was conducted in Simundol Village, Dolog Sigompulon District, North Padang Lawas Regency, North Sumatra Province. In this case researchers classify sources into two categories, namely primary sources and secondary sources and researchers collect data by means of observation, interviews and documentation. The results of this study are that morals are habits in everyday life which are the benchmark for the good and bad of one's actions. the views of the Islamic and Christian communities towards an act or action will be said to be moral if it is in accordance with the customs that apply in society and one of the goals is to help build morals, especially as a form of moral development in the Simundol Village community.